PENINGKATAN PEREKONOMIAN PETANI ANGGUR DI DESA BANJAR KECAMATAN BANJAR KABUPATEN BULELENG DENGAN MENERAPKAN IPTEKS YANG TEPAT GUNA - Tuningrat, I. A. M.; Arihantana, N. M. I. H.; Duniaji, A. S. (Buletin Udayana Mengabdi; Vol 15 No 2 (2016): Jurnal Udayana Mengabdi, 2016)
Expected objective in this IbM is an increase in the production capacity of 400-500 bottles / month to 1000 bottles / month and the improvement of the quality of processing of grapes. Increasing knowledge and skills of farmers in post-harvest handling of the grapes. Empowerment of farmers' management of business management grapes. The products can be sold with appropriate packaging labeling requirements. Longer shelf life of the product with a broader marketing reach. The movement of the economy of rural communities, community activities increased, the growth of farmers invitation partnership business unit and ultimately increased revenue and reduced poverty. Grape juice product has been tested against a component of vitamin C and Anthocyanin content in juice. Dodol products also performed testing of vitamin C and contains antosianinnya. The test results indicate that grape juice contains vitamin C as much as 5.456 mg per 100 g of material and anthocyanin content 8025 mg per 100 g of material, while lunkhead grapes contain vitamin C and anthocyanin content of each is 8.828 mg per 100 g of material and 82.760 mg per 100 g of material. Grape juice products and dodol already marketed. Market segment has been up stalls and outlets in the city of Singaraja and Denpasar. Both of these products have also been promoted within the campus of the University of Udayana during the workshop on Biodiversity of Agriculture on May 15, 2015. This product is highly preferred by consumers proved a number of 150 bottles at a price of Rp 7,000 sold, while lunkhead grapes at a price of Rp. 1,250 as many as 100 seeds. Prromosi also performed on Agricultural Products Festival exhibition held at the Badung regency Tukad Bangkung Pelaga, District of Badung regency evening the number of sales turnover dodol 4,000 seeds with a value of Rp 5,000,000 and products Juzy Grapes 1,000 bottles with a value of Rp. 7,000,000.
Keywords: grape juice; lunkhead grapes; wine; quality wine; grape products